Family Income, Cumulative Risk Exposure, and White Matter Structure in Middle Childhood - Dufford, Alexander J.; Kim, Pilyoung (Frontiers in Human Neuroscience, 2017)
Family income is associated with gray matter morphometry in children, but little is known about the relationship between family income and white matter structure. In this paper, using Tract-Based Spatial Statistics (TBSS), a whole brain, voxel-wise approach, we examined the relationship between family income (assessed by income-to-needs ratio) and white matter organization in middle childhood (N = 27, M = 8.66 years). Results from a nonparametric, voxel-wise, multiple regression (threshold-free cluster enhancement, p < 0.05, FWE corrected) indicated that lower family income was associated with lower white matter organization (assessed by fractional anisotropy) for several clusters in white matter tracts involved in cognitive and emotional functions including fronto-limbic circuitry (uncinate fasciculus and cingulum bundle), association fibers (inferior longitudinal fasciculus, superior longitudinal fasciculus), and corticospinal tracts. Further, we examined the possibility that cumulative risk exposure might function as one of the potential pathways by which family income influences neural outcomes. Using multiple regressions, we found lower fractional anisotropy in portions of these tracts, including those found in the left cingulum bundle and left superior longitudinal fasciculus, was significantly related to greater exposure to cumulative risk (β = -0.47, p < 0.05 and β = -0.45, p < 0.05).